Ergonomic optimization of a manual wheeled furrowing implement (IMRS) using user-centered design methodologies: a case study in Peruvian smallholder agriculture - Castillo Roque, Cesar Augusto; Yupanqui Leon, Wendy Carolina; Vasquez Llave, Trunks Giorgio; Canazas Rodriguez, Jose Carlos; Silva Vidal, Yuri Lester; Garate Delgado, Jose Fernando (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the manual wheeled furrowing implement (IMRS), a human-powered tool used by smallholder farmers in the Tiabaya district (Arequipa, Peru) to form furrows and hill crops of onion and garlic requiring 45 cm spacing, operated for up to 227 furrows per plot in 10–12 hour shifts. The unvarying height of the handle compels taller individuals to maintain prolonged trunk bending and wrist extension, while shorter users manage the excess force with their arms, structurally excluding women who lack a fitting handle height. Four approaches were employed: design thinking and quality function deployment (QFD) to translate farmer needs into key engineering goals; VDI 2221/2225 to evaluate design alternatives; the McKyes & Ali equation for modeling soil resistance in sandy loam found in Tiabaya; and Digital Human Models within CATIA V5 for biomechanical validation at female P5 and male P95 percentiles before physical prototyping. The refined design incorporates a Ø2" SCH10 tube frame with a quick-release height adjustment limited to between 900 and 1,200 mm based on QFD priorities, a Ø600 mm spoked wheel, an AISI 1045 heat-treated furrower, and handles made from AISI 304 steel, minimizing push force by 8%. This reduction occurs because the larger wheel distributes soil reaction over a broader area, lowering rolling resistance per the McKyes & Ali model. The adjustable height eliminates the postures causing a score of 5 on the rapid upper limb assessment (RULA), reducing it to 4 for users at both measurement extremes. While unit cost is higher (≈ S/680 vs. S/300–400), a lifespan exceeding 12 years yields break-even within 3–4 years, aligning with sustainable development goals (SDGs) 2, 5, and 8